2008
DOI: 10.1111/j.1600-0765.2008.01085.x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between periodontal condition and serum levels of resistin and adiponectin in elderly Japanese

Abstract: Background and Objective: Diabetes and periodontitis are associated with each other.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
87
1
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(104 citation statements)
references
References 31 publications
11
87
1
5
Order By: Relevance
“…IL-6 promotes osteoclast differentiation. 16 Furugen et al 23 found no significant difference in serum IL-6 levels in individuals with and without periodontitis, while higher levels have also been reported in periodontitis. 24 There is research showing that IL-6 inhibits adiponectin gene expression and secretion in 3T3-L1 adipocytes, indicating that it is implicated in adiponectin regulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-6 promotes osteoclast differentiation. 16 Furugen et al 23 found no significant difference in serum IL-6 levels in individuals with and without periodontitis, while higher levels have also been reported in periodontitis. 24 There is research showing that IL-6 inhibits adiponectin gene expression and secretion in 3T3-L1 adipocytes, indicating that it is implicated in adiponectin regulation.…”
Section: Discussionmentioning
confidence: 99%
“…9 There are studies 23,27,28 that have not shown statistically significant differences in serum adiponectin levels in periodontitis patients compared with healthy control individuals, while a recent article 29 showed a lower ratio of high-molecular-weight adiponectin to total adiponectin in patients with periodontal pockets; this ratio was independently associated with periodontal condition.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Shimada et al (18) found a positive correlation between leptin levels and the following clinical parameters: PD, CAL, bone loss and BMI, which sustain the inflammatory role of this adipokine. Furugen et al (16) found a positive correlation between BOP and resistin, which indicates its presence in inflammation. They found a significant but weak negative correlation between adiponectin levels and CAL; this result the authors credited to the low levels of adiponectin observed in males with severe clinical attachment loss.…”
Section: Discussionmentioning
confidence: 99%
“…33 Son 10 yılda resistin seviyesinin KP, T2DM ve obezite ile ilişkisini değerlendiren birçok çalışma yapılmıştır [34][35][36][37][38][39][40][41] (Tablo 1). Bunların bir kısmında, sadece KP'si olan bireylerde; 34,35 bazılarında ise KP'ye ilave olarak T2DM 36,38 veya obezite 37,39,41 varlığında resistin seviyeleri araştırılmıştır. Çalışmaların çoğunda sistemik olarak sağlıklı KP hastalarında serum resistin seviyesinin periodontal olarak sağlıklı bireylere kıyasla daha yüksek olduğu bildirilmiştir.…”
Section: Resim 1 Periodontitis Tip 2 Diabetes Mellitus Ve Insülin Dunclassified